21st Mediterranean Conference on Control and Automation 2013
DOI: 10.1109/med.2013.6608765
|View full text |Cite
|
Sign up to set email alerts
|

Control structure design for complex energy integrated networks using graph-theoretic methods

Abstract: In this paper, we propose a mixed integer program (MIP) formulation which can be used to synthesize multi-loop hierarchical control structures for tightly energy integrated plants, which are known to exhibit multiple-time scale energy dynamics. First, we represent the network as an energy flow graph, and perform graph reduction using graph-theoretic algorithms that we have previously developed, to analyze the time scale properties of the network and obtain energy flow subgraphs for each time scale. Then, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Based on this information, a hierarchical control strategy can be used to control the energy dynamics of the network. For example, it was shown that the energy dynamics of the HDA network can be controlled using simple PI controllers, addressing different control objectives in different time scales as summarized in Table . Also, the reduced models derived above can be used to design nonlinear model‐based controllers.…”
Section: Energy‐integrated Reactor‐heat Exchanger Networkmentioning
confidence: 99%
“…Based on this information, a hierarchical control strategy can be used to control the energy dynamics of the network. For example, it was shown that the energy dynamics of the HDA network can be controlled using simple PI controllers, addressing different control objectives in different time scales as summarized in Table . Also, the reduced models derived above can be used to design nonlinear model‐based controllers.…”
Section: Energy‐integrated Reactor‐heat Exchanger Networkmentioning
confidence: 99%